Artists, Emotions and Creativity: An Analytical Study of Artist’s life in Pakistani Muslim Society (Al-Qamar, 2021)
This article narrates the persona of an artist and how emotion becomes the core value of his creativity. His emotional comforts and discomforts provide him a podium to build an edifice of his experiences in the form of art. The artist takes responsibility to express the emotions of mankind and creates art with complexities or ease but he finds a kind of joy in it. Through his emotional response he reveals the humanity and librates us from narrow confines of our limited perceptions.
Keywords: Art and Emotion; artists and creativity; who is the artist; emotions is the core of art